Evaluation of the nutritional value and active compounds of commercial and non-commercial oilseed meals - Saeed Mollaei; Seyed Mortaza Hosseini-Nami; Saeid Hazrati (Scientific Reports)
Abstract Cold pressing is one of the most common methods of extracting oil from seeds, generating by-products in the form of meals that are often discarded as waste. Given the large quantities of these meals and the presence of valuable compounds, a thorough investigation of their nutritional value and potential applications is essential. The aim of this study was to evaluate and compare the residual oil, total phenol and flavonoid content, phenolic compounds, antioxidant activity, as well as the ash, carbohydrate, protein, and mineral nutrient content of 15 commercial and non-commercial oilseed meals. The results showed that Sesamum indicum meal had the highest residual oil content (17.86 ± 2.4%). Among the meals studied, Pistacia atlantica showed the highest concentrations of phenols (17.67 ± 0.69 mg GAL/g meal) and flavonoids (3.07 ± 0.003 mg QE/g meal). Also, it exhibited the highest DPPH radical scavenging activity, with an IC50 value of 33.11 ± 1.41 µg/mL. Quantitative HPLC analysis showed that P. atlantica and Helianthus annuus meals were particularly rich in quercetin (37.20 ± 2.97 mg/g meal) and rosmarinic acid (46.67 ± 3.32 mg/g meal), respectively, suggesting that their antioxidant properties may be due to these compounds. In terms of macronutrients, the highest carbohydrate content was observed in Arachis hypogaea (37.92 ± 0.11%), while H. annuus meal had the greatest protein concentration (45.12 ± 1.83%). Mineral analysis showed that Prunus armeniaca, H. annuus, and Chrozophora tinctoria meals were the richest sources of potassium (1.73 ± 0.04%), phosphorus (0.60 ± 0.03%), and calcium (16.20 ± 0.09%), respectively. Furthermore, the highest magnesium content (0.29 ± 0.00%) was found in Cucurbita pepo and Lallemantia royleana meals. These findings highlight the nutritional and bioactive potential of the meals studied, especially those from P. atlantica, H. annuus, and L. royleana, which contain valuable compounds suitable for applications in food, cosmetics, pharmaceuticals, and other industries.